2021
DOI: 10.5433/1679-0359.2021v42n3supl1p2023
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality and technological potential of pitaya species

Abstract: Hylocereus costaricensis, H. undatus, and H. megalanthus are pitaya species produced and marketed in Brazil. The cultivation of this fruit has increased in recent years owing to its attractive appearance and sweet taste, and it may be either consumed fresh or processed for beverages and desserts. Studies on the biochemical traits and antioxidant capacity of these species can contribute to the development of new pitaya cultivars for fresh consumption and/or industrial processing. Sugars and organic acids were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In a comparison of three species (H. costaricensis, H. undatus and H. megalanthus), the content of total phenolics in the pulp was 33, 23 and 22 mg gallic acid eq. 100 g −1 , H. costaricensis being the fruit with the highest antioxidant activity, 15-fold higher than H. undatus and H. megalanthus [61]. The three species differ in the colour of the peel and flesh, and it can be concluded that total phenol content and antioxidant capacity are notably higher in red-fleshed fruits than white-fleshed fruits.…”
Section: Discussionmentioning
confidence: 89%
“…In a comparison of three species (H. costaricensis, H. undatus and H. megalanthus), the content of total phenolics in the pulp was 33, 23 and 22 mg gallic acid eq. 100 g −1 , H. costaricensis being the fruit with the highest antioxidant activity, 15-fold higher than H. undatus and H. megalanthus [61]. The three species differ in the colour of the peel and flesh, and it can be concluded that total phenol content and antioxidant capacity are notably higher in red-fleshed fruits than white-fleshed fruits.…”
Section: Discussionmentioning
confidence: 89%
“…Each 100.0 g H. megalanthus fruit pulp contains 22.90 mg GAE total phenolic content, 13.07 g carbohydrates, 1.27 g fiber, 0.10 g of fat, 0.40 g protein, 17.99 mg phosphorus, 98.41 mg potassium, 11.73 mg calcium, 16.09 mg magnesium, 1.43 mg sodium, 4.35 mg zinc, 21.07 mg iron, 0.20 mg niacin, 5.93 g total sugar, and 11.34 mg of vitamin C [28], as well as volatile compounds such as alcohols, terpenes, paraffins, acids, esters, ketones, and odor-active compounds that influence flavor [29]. [ [24][25][26]30,31] [ 24,31,32] [ 28,33] Note: The nutritional composition between different species, geographical locations, and methods of determination may differ.…”
Section: Nutritional Compositionmentioning
confidence: 99%